ANALISIS PERAN ORANGTUA DALAM PENGENALAN PENDIDIKAN SEKS REMAJA DI KAMPUNG KAPUR PONTIANAK - Siti Handayani; Sulistyarini Sulistyarini; Imran Imran (Universitas Tanjungpura, 2019)
AbstractThis study was conducted to explain and analyze the role of parents in introducing sex education to teenagers in Kampung Kapur, Banjar Serasan, East Pontianak. This study aims to determine parental understanding of sex education, how parents carried out their role as educators, friends, and counselors in introducing sex education. This study used a qualitative approach with descriptive method. The sources of this research were parents and teenagers in Kampung Kapur. The results of the study indicate that; 1) the role of parents as educators in introducing sex education to teenagers and played a role in educating their children. Parents gave about sex and moral values, mass media, and religious values to their children in the form of advice and prohibitions, 2) the role of parents as friends in introducing sex education to teenager had not played well where parents still lack of knowledge about sexual transmitted diseases. Therefore, there was no explanation from the parent to their children, 3) the role of parents as counselors in introducing sex education to teenager showed that the parents did not have enough understanding about sex such as puberty, fertility, function and reproductive health, they were still considered this as taboo.Keywords: Role of Parents, Sex Education, Teenagers.